Dicephalus dipus dibrachius: conjoined twins through the ages. Issue 1 (February 2014) - Miceli, Frances
Abstract: Conjoined twins are the most rare form of monozygotic twinning occurring when there is incomplete division of the embryonic disc after day 13 post conception. This is associated with a very high risk of perinatal morbidity and mortality. Prognosis is dependent on the site and extent of fusion and the degree of sharing of vital organs. Most conjoined twins die in utero or in the early neonatal period. However less severe cases can be successfully separated. This is a review of the types of conjoined twinning, an historical perspective and a case of a rare form known as dicephalus dipus dibrachius (two heads and a single body with two arms and two legs).